Electrical Load Control Using PIR Sensor for IoT-based Electrical Power Saving - Suprianto; Frianto, Heri Trisna; Abidin, Ahmad Farid Bin; Idros, Mohd Faizul bin Md; Razak, Abdul Hadi Abdul (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Wasteful use of electrical energy, apart from the use of electrical loads, is also caused by wasteful and uncontrolled use of electrical loads. Electrical energy that is not used as needed causes electricity waste. This research aims to use the IoT system for electrical automation and monitoring the amount of electricity in a room. In this way, saving electricity and monitoring the amount of electricity can be done easily through the IoT system at anytime and anywhere. The method used in this research is an experimental method, namely designing equipment according to the planned system and preparing a program according to the desired tool working system. The research object is the electrical load in three rooms consisting of three load groups, each load group is represented by a PIR sensor light, namely the equipment used is the PZEM sensor, PIR sensor, RTC, ESP 32, Triac, Optocoupler, and other supporting equipment. The results of the research show that the equipment has worked well and has been tested well, electricity savings are shown through the monitor on the Android cellphone using the Blynk application which was previously installed. Every time there is a person in the room, the PIR sensor always detects the object and activates the electrical load and vice versa. Apart from that, the cellphone monitor screen also displays from time to time the amount of electricity used by the load, including the electrical energy used and the electrical energy savings that can be done.